Determination of heavy metals in cigarettes using high-resolution continuum source graphite furnace atomic absorption spectrometry. Issue 27 (28th June 2017) - Ren, Ting; Chen, Xi; Ge, Yao; Zhao, Lijiao; Zhong, Rugang
Abstract : Quantitative determination of toxic metals in tobacco, smoke, ash and butts of cigarettes using HR-CS GFAAS. Abstract : Heavy metal contamination induced by cigarette smoking is a critical issue in environmental pollution and human health risk. Although a number of investigations have been performed on the detection of heavy metals in cigarette tobacco, only very limited data have been reported for the determination of these metals in other parts of cigarettes. In this study, the contents of copper, cadmium, chromium, nickel and lead in cigarette tobacco, smoke, ash and butts were quantified using high-resolution continuum source graphite furnace atomic absorption spectrometry. The LODs for Cu, Cd, Cr, Ni and Pb were 0.010 μg L −1, 0.020 μg L −1, 0.025 μg L −1, 0.030 μg L −1 and 0.012 μg L −1, respectively. Twelve cigarette samples purchased from eleven popular brands in China were used for the heavy metal measurements. Microwave digestion was employed for the preparation of the cigarette tobacco, ash and butt samples. A smoke collection apparatus, which was designed to simulate human smoking behavior by alternating suction and pause intervals, was used to capture the heavy metals in smoke. The total amounts of the determined metals were observed to be the highest in ash (55.60 to 125.99 μg g −1 ), followed by tobacco (11.70 to 22.34 μg g −1 ) and butts (4.29 to 15.22 μg g −1 ), and were 0.67, 0.10, 0.14, 0.16 and 0.24 μg per cigarette for Cu, Cd, Cr, Ni and Pb, respectively, in smoke. The residual rates of the heavy metals in ash, smoke and butts were measured to estimate the distribution of each element after the cigarette tobacco was fully burnt. The results indicated that the majority of the heavy metals (41.1% to 68.7%) remained in ash, with 10.0% to 28.0% condensed in butts and 6.6% to 22.9% released into the mainstream smoke. Moreover, a high variance of the five metal contents was observed in different brands of cigarettes, which might be associated with the geographical origin of the tobacco plant, cigarette production procedure, and transportation and storage of the materials and products. This study provides a reliable method for the quantitation of heavy metals in different components of cigarettes, which will be beneficial to the prevention of heavy metal hazards and the reduction of human health risks through tobacco consumption.